"Exploring the Potential of the Israeli Model: A Comparative Analysis of Azerbaijani and Israeli Diaspora Efficiency and its Implications for the Azerbaijani Diaspora's Future Activities" - Mammadova, Nigar; Mardanov, Elnur; Miri, Mirulvi (ADA University, 2023)
Diasporas play an essential role in shaping global politics, economics, and culture and in light of the development and efficiency improvement of Azerbaijani Diaspora this paper aims to analyze challenges that Azerbaijani Diaspora faces. The study has revealed that Azerbaijan has a great potential to improve its Diaspora through the implementation of world practices. The study poses solutions for each challenge - establishment of an organization, creating a climate for better lobbying, creation of digital tools for awareness purposes. All these solutions are evaluated according to five main criteria such as effectiveness, efficiency, equity, feasibility/implement ability, and flexibility/improvability. The research includes secondary data from various sources and semi-structured interviews with experts in the relevant field. The analysis and assessment show that each problem should be addressed separately and solutions presented in the paper should go in parallel. Each of the solutions elaborates on a specific issue, which can be successful if implemented together. While the creation of a stronger community focuses on the challenges related to absence of legal framework, better lobbying changes address the political issue. Lastly, communication challenges that arise in the globalized world should be dealt with in order to be able to implement the previously mentioned problems.
Keywords: Public and International Affairs; Diaspora -- Israel.; Diaspora -- Azerbaijan.; Diaspora strategy.